Effect of mixing state of binary particles on bubble behavior in 2D fluidized bed. Issue 8 (3rd August 2018) - Chen, Hengzhi; Tian, Xiaoxue; Gu, Sumin; Geng, Chao; Yang, Dongming
ABSTRACT: In this study, a thin 2D fluidized bed was used to investigate the effect of mixing state of the binary particles on bubble behavior through the analysis of images captured by a high-speed digital camera. Experimental results show that the mixing index increases gradually with increasing gas velocity and the binary particles are in different mixing states though they are in the steady fluidization state. The maximal bubble number is near the interface of the bed when the binary particles are in the segregation state, whereas the maximal bubble number is at the bottom when the binary particles are in the well mixing state. The small bubbles are position at the bottom and are adjacent to the bed wall, while the large bubbles are mainly located in the central regions of the bed. The average bubble diameter shows the different variation trends with the different mixing states of the binary particles. The correlations estimating bubble diameter according to the mixing state of the binary particles are developed, and the computing value agrees well with the experimental data.